Role B4C Addition on Microstructure, Mechanical, and Wear Characteristics of Al-20%Mg2Si Hybrid Metal Matrix Composite - Hamidreza Ghandvar; Mostafa Abbas Jabbar; Seyed Saeid Rahimian Koloor; Michal Petrů; Abdollah Bahador; Tuty Asma Abu Bakar; Katsuyoshi Kondoh (Applied Sciences, 2021)
In the current study, the effect of different B4C additions (0, 2.5, 5, and 10 wt%) on the microstructural, solidification behavior, mechanical, and tribological properties of Al-20%Mg2Si composite were studied by means of scanning electron microscopy (SEM) equipped with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), Vickers hardness, tensile, and dry sliding wear tests. The cooling curve thermal analysis (CCTA) approach was utilized to monitor the influence of B4C particles on the solidification behavior of Al-20%Mg2Si composite. The results revealed that the addition of B4C particles up to 10 wt% reduced the nucleation temperature (TN) and growth temperature (TG) of the primary Mg2Si phase. Moreover, the proper amount of B4C added to Al-20%Mg2Si composite has a significant effect on the microstructural alteration, mechanical, and tribological properties of the composite. The mean size of primary Mg2Si in Al-Mg2Si composite was 47 μm, in which with the addition of 5 wt% B4C, the particle size decreased to 33 μm. The highest UTS (217 MPa) and El% (7%) was achieved in Al-20%Mg2Si-5%B4C hybrid composite. The cast Al-20%Mg2Si composite revealed the brittle mode of fracture with some cleavage characterization, in which with the addition of 5%B4C, the fracture mode altered to a more ductile fracture. The wear results revealed that the Al-20%Mg2Si-5%B4C hybrid composite has the highest wear resistance with the lowest wear rate (0.46 mm3/Km) and friction coefficient (µ = 0.52) under 20 N applied load compared to other fabricated composites with mild abrasion as the governed wear mechanism.